Two new compounds from the aerial parts of Elsholtzia densa. (December 2022) - Yang, Jiaying; Du, Jiangchao; Yu, Fei; Li, Rongtao; Zhong, Jindong
Abstract: Two new compounds, named edensa acid (1 ), and edensaoside A (2 ), as well as twenty-nine known compounds (3–31 ) were isolated from the aerial parts of Elsholtzia densa Benth. The chemical structures of the new compounds were determined by spectrometric data interpretation using NMR, HRESIMS, IR and UV spectroscopy. In addition, all compounds were evaluated for their anti-influenza virus activities against A/WSN/33(H1N1). Among these, compounds 18 and 19 exhibited moderate anti-influenza virus activities with IC50 values of 18.79 μ M and 59.87 μ M respectively. Graphical Abstract: ga1 Highlights: Two new and twenty-nine known compounds were isolated from the aerial parts of Elsholtzia densa Benth. Structures were elucidated by spectroscopic analysis. Compounds were evaluated for their anti-influenza A virus activities.